Pricing vanilla options using artificial neural networks: Application to the South African market - Ryno Du Plooy; Pierre J. Venter (Cogent Economics & Finance, 2021)
In this paper, a feed-forward artificial neural network (ANN) is used to price Johannesburg Stock Exchange (JSE) Top 40 European call options using a constructed implied volatility surface. The prices generated by the ANN were compared to the prices obtained using the Black-Scholes (BS) model. It was found that the pricing performance of the ANN significantly improves when the number of training samples are increased and that ANNs are able to price European call options in the South African market with a high degree of accuracy.
Keywords: 330; Artificial intelligence; European call options; financial derivatives; implied volatility; Johannesburg Stock Exchange (JSE); machine learning; neural networks